Self-translation : brokering originality in hybrid culture - Cordingley, Anthony (London : Bloomsbury, 2013)
Examines writers and artists negotiating their multilingual cultural contexts and hybrid identities when producing works in one language which they then translate into another. This book establishes an understanding of the heterogeneity of this form of cultural production known as self-translation.
Part 1. Self-translation and literary history -- 1. The self-translator as rewriter -- 2. On mirrors, dynamics and self-translations -- 3. History and the self-translator - Part 2. Interdisciplinary perspectives: sociology, psychoanalysis, philosophy -- 4. A sociological glance at self-translation and self-translation -- 5. The passion of self-translation: a masocritical perspective -- 6. Translating philosophy: Vilem Flusser's practice of multiple self-translation -- Part 3. Post colonial perspectives -- 7. Translated otherness, self-translated in-betweens: hybridity as medium versus hybridity as object in Anglophone African writing -- 8. Why bother with the original? : self-translation and Scottish Gaelic poetry -- Indigenization and opacity: self-translation in the Okinawan/Ryukyuan writings of Takara Ben and Medoruma Shun -- Part 4. Cosmopolitan identities/texts -- 10. Self-translation, self-reflection, self-derision: Samuel Beckett's bilingual humor -- 11. Writing in translation: a new self in a second language -- 12. Self-translation as broken narrativity: towards an understanding of the self's multilingual dialogue.
Includes bibliographical references and index.
Keywords: MULTILINGUIALISM -- SOCIAL ASPECTS; MULTILINGUIALISM AND LITERATURE; SIMULTANEOUS INTERPRETING; LANGUAGE AND CULTURE; SELF-TRANSLATION; TRANSLATING AND INTERPRETING